Effect of EDTA Gel on Residual Subgingival Calculus and Biofilm: An In Vitro Pilot Study - Charles M. Cobb; Stephen K. Harrel; Donggao Zhao; Paulette Spencer (MDPI AG, 2023)
Background: Residual calculus, following scaling and root planing (SRP), is associated with persistent inflammation and the progression of periodontitis. This study examined the effects of a 24% neutral ethylenediaminetetraacetic acid (EDTA) gel on subgingival calculus and biofilms. Methods: Eleven single-rooted teeth extracted because of severe periodontal disease were randomly assigned to the following treatment groups: (1) three teeth served as untreated controls; (2) three teeth were treated by scaling and root planing (SRP) only; and (3) three teeth were treated by SRP + EDTA. The remaining two teeth, one SRP only and the other SRP + EDTA were designated for energy-dispersive X-ray spectroscopy (EDS) analysis. EDTA gel was placed on the SRP surface for 2 min and then burnished with a sterile cotton pellet. Results: SRP + EDTA treated specimens exhibited severely damaged biofilm and the disruption of the extracellular polymeric matrix. EDS scans of the smear layer and calculus featured reductions in the Weight % and Atomic % for N, F, Na, and S and increases in Mg, P, and Ca. Conclusions: A 25% neutral EDTA gel was applied after SRP severely disrupted the residual biofilm and altered the character of dental calculus and the smear layer as shown by reductions in the Weight % and Atomic % for N, F, Na, and S and increases in Mg, P, and Ca.